On Assessing a Firm's Cash Generating Ability. - Stephens, Ray G.; Govindarajan, Vijay; Barrett, M. Edgar (The Accounting Review, 1990)
Focusing on funds flow from operations, a way for analysts to use financial statement information to obtain additional insights when assessing a firm's cash generating ability is proposed. The method provides a clearer focus on a firm's cash generating ability from operations. Results from applying the proposed method are compared with information from traditional funds flow statements (APBO No. 19 and SFAS No. 95) for 20 firms, highlighting the incremental insights available.